Teaching Year Six Boys to Write: A Case Study of Two Melbourne Schools - Jennifer L Sze (Educational Considerations, 2025)
The debate surrounding boys’ literacy performance remains a complex and ongoing issue among policymakers, researchers, and educators. This study examines how two different schools nurture boys’ writing skills in Year 6. Writing, a crucial life skill in the 21st century, is essential for personal and professional success. Despite evolving perspectives on the gendering of writing, it is important to recognise that gender is a social and cultural construct. Educators must critically reflect on their own gender biases, avoid stereotyping students’ reading and writing abilities based on gender, and encourage all children to reach their full potential as readers and writers. Effective education is not only about academic achievement but also about cultivating children who are kind, compassionate, and equipped with communication skills—both reading and writing—that will enable them to lead fulfilling lives after school. This study investigates how a holistic school culture supports boys’ writing and explores various pedagogical strategies. It also offers insights into how teachers use technology and diverse approaches to enhance boys’ writing development.
Keywords: Elementary Writing; Boys& #x27; Writing; Engagement; Teacher Identity; Boys& #x27; Motivation; Motivation in Writing